Assessment of Degenerative Changes in Superficial Digital Flexor Tendon in Clinical Normal Horses - Tmumen, Samer K. (2005)
The equine tendon is a highly specialized cord that ensures optimal transmission of movements from muscles to bones. The tendon is elastic, capable of easily resuming its original shape after being stretched and resistant to stretching under physiological condition. Flexor tendons show a high incidence of partial central core rupture preceded by degeneration. Thus, injuries of superficial digital flexor tendon (SDFT) are common in athletic horses. Equine tendons were isolated from the forelimbs of 45 normal thoroughbreds consisting of 13 young, 22 middle and 10 old aged horses. The sex distribution was not taken into account. The horses were euthanised and forelimb tendon samples obtained. Gross examination showed tendon discolouration suggesting presence of degeneration in the apparently normal tendon. Tendon samples were obtained from the central core of the mid-metacarpal region of the forelimb SDFT. The fixed SDFT samples were processed and embedded in wax using a technique modified for the study and stained with haematoxylin and eosin (H&E) stain. All sections were examined under light, confocal laser microscopic and image analysis techniques. When the degenerative changes in the h orse forelimb SDFT were compared, the left SDFT showed more degenerative changes than the right. This reflects the local racing condition which is conducted in anti-clockwise manner. This study also showed that the degree of degenerative changes was higher (Pc0.05) in old horses compared to young horse, but not higher than the middle aged horses. Tendon thickness was compared using the ultrasonography and caliper methods. The mean values for the thickness of the forelimb SDFT obtained using the caliper method (23.3 k1.7 mm) were at least 25% greater than those obtained using the ultrasound method (17.2 k 2.1 mm) suggesting an overestimation of the caliper method. Measurements using the caliper are obviously less accurate because it measures the thickness of the tendon as well as the thickness the skin and the underlying tissues. The width of the SDFT measured by ultrasonography is by transverse scans only.The rate of healing of SDFT was compared in thoroughbreds and ponies. The SDFTs of five thoroughbreds and five ponies were injured surgically. The healing of each SDFT was monitored for six months. After six months, SDFT in ponies showed a complete healing, whereas in the thoroughbreds, granulation tissue was still clearly evident. The results showed that SDFT of ponies healed faster than that of thoroughbreds. The tendon and muscle samples of thoroughbreds and ponies were analysed for lactic acid (LA). The tendon of thoroughbreds has a higher resting LA concentration (3.04k0.42 mmoUL) than the ponies (1.45k.0.12 mmolIL) and increased to (7.45*0.71 mmol1L) and (3.42 k0.89 mmol/L) in thoroughbreds and ponies. Similarly, the muscle of thoroughbreds had a higher resting LA - - concentration (13.63 & 1.33 mmollL) than the ponies (1.82 k 0.09 mmol/L) and -- increased to 27 * 3.94 mmol/L and 18.91 * 5.35 mmol/L in thoroughbreds and ponies respectively after exercise. The increase of activity in muscle is reflected in a similar increase in the LA content of SDFT suggesting that the accumulation of LA in the tendon was the result of increased muscle LA production from increased a ctivity. The accumulation of LA m ay render the tendon p rone to injury. This study suggested that tendon degeneration showed a greater intensity in the left than the right SDFT. While thoroughbreds had a greater resting tendon and muscle LA concentration than ponies. This may be related to the fact that thoroughbreds have a greater muscle mass and higher physical activity than ponies. Plasma creatine kinase (CK) and plasma aspertate aminotransferase (AST) concentrated in horses are not good indicators of the increase in muscle activity.